MANAJEMEN STRATEGI GURU DALAM MENUMBUHKAN KESADARAN SISWA UNTUK MEMPERTAHANKAN PROGRAM ADIWIYATA DI MADRASAH TSANAWIYAH NEGERI 2 PAMEKASAN - Ahmad Rofiqi; Usman Usman (Prodi MPI Fakultas Tarbiyah IAIN Madura, 2020)
Strategic management is a series of processes or stages. The strategic management process provides managers with a combined framework for dealing with a variety of unique problems to identify new opportunities more easily and to estimate the strengths that could be used and weaknesses that should be corrected. This research uses a qualitative approach with descriptive type, the source of which is data obtained through interviews, observation, and documentation. The results showed that the teacher's strategic management in growing students' awareness to maintain Adiwiyata program, namely 1) Planning 2) Implementation 3) Evaluation every 3 months once. The supporting factors are: 1) Cooperation and cooperation between all elements of the school, 2) Following the existing regulations in school 3) Creating POKJA, 4) forming a picket schedule to monitor cleanliness, 5) Students do come from Adiwiyata elementary schools, 6) All teachers applying the Adiwiyata program to learning and organizational life. Inhibiting factors, namely: 1) The teacher's ignorance of the program and behavior that leads to the Adiwiyata program, 2) Family factors.